Prolotherapy in Chronic Coccydynia - Edlin; Sinaga, Mual Kristian (CoinReads Media Prima, 2023)
Introduction: Coccydynia, or coccygodynia, is pain in the tailbone or coccyx area. Despite identifying chronic coccyx pain happened hundreds of years ago, its treatment can be difficult and sometimes controversial due to the multifactorial nature of coccyx pain. Many physiological and psychological factors contribute to its etiology. Most cases of coccydynia resolve within weeks to months with or without conservative treatment, but for some patients, the pain could be chronic and bothersome. Cases: This report describes a patient who experienced a traumatic fall from a height, causing chronic coccyx pain. Coccyx pain is local and does not radiate, usually gets worse when changing from sitting to standing or vice versa. This makes it difficult for patients to carry out their usual activities. After taking pain medications regularly for years, the pain does not improve. Conclusion: Prolotherapy is an injection therapy for chronic musculoskeletal injuries, including coccydynia. Injection prolotherapy aims to tighten and strengthen weak or lax tendons, ligaments, or joint capsules through the multiplication and activation of fibroblasts. The main principle is the injection of small amounts of irritant solution into the painful ligament and tendon insertions as well as in the adjacent joint space over several treatment sessions. This technique has been shown to reduce patient pain by approximately 50% of initial pain after the first session of prolotherapy. It is hoped that the repetition of this session will further reduce and even eliminate the chronic pain that the patient has been suffering.